Comparative Studies of the Physical, Mechanical and Chemical Properties of Hybrid Coatings for Medical Implants; AIP Conference Proceedings; Vol. 1882 : Physics of Cancer: Interdisciplinary Problems and Clinical Applications (PC IPCA’17) - Kharapudchenko E. A. Elena Aleksandrovna; Ignatov V. P. Viktor Pavlovich; Kozelskaya A. I. Anna Ivanovna; Tverdokhlebov S. I. Sergei Ivanovich (2017, 2017)
Title screen